HUBUNGAN ANTARA KEPERCAYAAN DIRI DAN KEMAMPUAN KOMUNIKASI MATEMATIS TENTANG MATERI BANGUN RUANG SISWA KELAS V SD NEGERI SE-KECAMATAN ALIAN - Nurlia Agustin; Suhartono Suhartono; Salimi Salimi (Journal of Professional Elementary Education, 2022)
The study aimed to analyze the correlation and contribution self-confidence and mathematical communication skills about solid figures to fifth grade students of public elementary schools in Alian Sub-district in academic year of 2020/202. It was correlational quantitative method. The samples were 289 fifth grade students in 11 public elementary schools throughout the Alian Sub-district. Sampling method was  a cluster random sampling. Data analysis used SPSS application. The results showed that the correlation between self-confidence and mathematical communication skills had correlation coefficient 0.595. The contribution was 35.4%. It concludes that there is positive and significant correlation between self-confidence and mathematical communication skills. It means that the higher student’s self-confidence, the higher student’s mathematical communication skills and vise versa. Self-confidence contributes 35.4% on mathematical communication skills about solid figures and the remaining 64.6% is influenced by other factors